First Record of the Monogenean Gyrodactylus lavareti Malmberg, 1957 in Iraq on Gills of the Common Carp Cyprinus Carpio - Abdul-Ameer, Kefah. N.; Al-Saadi, Abid Ali. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The monogenean Gyrodactylus lavareti Malmberg, 1957 is recorded here in the present study for the first time in Iraq from gills of the common carp Cyprinus carpio. This is the twentieth gyrodactylid species to be recorded from fishes of Iraq. The description and measurements of this parasite as well as its illustration were given.